Probing the Equivalence of Mental Process in a Novel The Nameless Ones: An English - Indonesian Annotated Translation - Melati Nurjana; Ni Luh Putu Setiarini (International Journal of English and Applied Linguistics (IJEAL), 2024)
This study is an annotated on the translation of English mental processes in a novel The Nameless Ones into Indonesian. The study aims to examine the equivalence of English mental process, categories of mental processes, translation strategies, and translation principles. The source of data was the novel The Nameless Ones. It was written by John Connoly and published in 2021. The data of this study were the English mental processes and their equivalences in Indonesian. The total number of the data was 100 data. The methods applied were qualitative and quantitative. The approaches were introspective and retrospective approach. The findings show that there were four categories of mental processes found in the novel, namely cognition, perception, emotion, and volition. The highest number of mental processes was cognition, the second place was emotion, the third was perception, and the least was volition. On the other hand, there were eight translation strategies applied in translating the English mental process. They were literal translation, unit shift, distribution change, clause structure change, transposition, calque, emphasis change, and antonymy. The most used strategy was literal translation since most of the mental processes could be translated literally by using the closest equivalents. On the contrary, the least used strategy was antonymy. This study implies that in translating the source text into the target text, the translator should comprehend the translation strategies and other theories relating to translation in order to produce a good quality of translation.